Mechanical caracterisation of polyester resin and corn natural fibers composite - Queijo, Luis (2012)
The use of natural fibers as reinforcement in polymer matrix composites is gaining popularity in the development of renewable products. Although glass and other synthetic fiber-reinforced plastics possess high specific strength, their fields of application are very limited because of their inherent higher cost of production. The work deals with the characteristics of fiber composites that can offer several advantages, like low cost, weight savings and relatively good mechanical properties. It focuses on the effects of corn fibers as reinforcement agents in composites. Mechanical testing was performed to qualify the reinforcement properties of the corn fibers and consequently to compare with fiberglass composites.